Empagliflozin (an SGLT2 inhibitor), alone or in combination with linagliptin (a DPP-4 inhibitor), prevents steatohepatitis in a novel mouse model of non-alcoholic steatohepatitis and diabetes. Issue 1 (December 2016) - Jojima, Teruo; Tomotsune, Takanori; Iijima, Toshie; Akimoto, Kazumi; Suzuki, Kunihiro; Aso, Yoshimasa
Abstract Background Sodium-glucose co-transporter-2 (SGLT2) inhibitors are new oral antidiabetic drugs that reduce hyperglycemia by promoting urinary glucose excretion. Glycosuria produced by SGLT2 inhibitors is associated with weight loss, mainly due to reduced fat volume. We investigated the effects of empagliflozin (selective SGLT2 inhibitor) and linagliptin (DPP-4 inhibitor) on steatohepatitis and fibrosis in a mouse model of non-alcoholic steatohepatitis (NASH) with diabetes. Methods A novel NASH model was generated by administration of streptozotocin to C57BL/6J mice at 2 days old, with a high-fat diet from 4 weeks. NASH mice aged 6 weeks were divided into four groups of 6 animals: vehicle, linagliptin (10 mg/kg), empagliflozin (10 mg/kg), and linagliptin + empagliflozin. The histological non-alcoholic fatty liver disease activity score was significantly lower in the empagliflozin and linagliptin + empagliflozin groups than in the vehicle or linagliptin groups. Hepatic expression of inflammatory genes (tumor necrosis factor-α, interleukin-6, and monocyte chemoattractant protein-1) was decreased in the empagliflozin and linagliptin + empagliflozin groups compared with the vehicle group. The collagen deposition with Sirius red staining was significantly reduced in the linagliptin + empagliflozin group compared with the linagliptin or the empagliflozin group. Immunohistochemistry showed that expression of α-smooth muscle actin, a marker of myofibroblasts (fibrosis), was reduced in the linagliptin + empagliflozin group compared with the vehicle group, as was expression of type 1 and 3 collagen mRNA. Linagliptin + empagliflozin decreased expression of mRNAs for genes related to fatty acid synthesis, but did not increase mRNAs for β-oxidation-related genes. Conclusions While empagliflozin alone attenuates development of NASH showing anti-steatotic and anti-inflammatory effects, combined administration of empagliflozin and linagliptin can synergistically ameliorates NASH with stronger anti-fibrotic effects.